Tropical forest conservation efforts as climate change mitigation in Indonesia: A Review - Adnan, Bahana Aditya; Dadi, Dadi (Interdisciplinary International Journal of Conservation and Culture, 2023)
Climate change affects forests both directly and indirectly through disturbances. Disturbances are a natural and integral part of forest ecosystems, and climate change can alter these natural interactions. When disturbances exceed their natural range of variation, the change in forest structure and function may be extreme. Each disturbance affects forests differently. Reducing Emissions from Deforestation and Forest Degradation (REDD+) is a global initiative aimed at curbing carbon emissions from forest cover change. Indonesia, one of the most biodiverse places on the planet with the third largest extent of tropical forest, has been extensively involved in REDD+. Despite commitments from the government of Indonesia and the international community, the deforestation rate has not stabilized or decreased in the years since REDD+’s introduction in 2007. Although there is an extensive body of literature on REDD+, the need for grounded observations from the field could clarify existing challenges and inform future pursuits. Challenges identified for each criterion include a lack of sufficient funding opportunities, inability to enforce boundaries due to corruption, and lack of a solid plan for involving communities. Carbon sequestration and biodiversity preservation results were mixed because of a lack of monitoring and problems with encroachment. We argue that changes must be made to Indonesian policy to help enable the enforcement of project boundaries, monitoring technologies should be utilized, and stakeholders, particularly at the national level, need to address some of the challenges discussed to achieve effective REDD+ outcomes in the future.